2019
DOI: 10.1126/scisignal.aax1872
|View full text |Cite
|
Sign up to set email alerts
|

Engineering γδT cells limits tonic signaling associated with chimeric antigen receptors

Abstract: Despite the benefits of chimeric antigen receptor (CAR)–T cell therapies against lymphoid malignancies, responses in solid tumors have been more limited and off-target toxicities have been more marked. Among the possible design limitations of CAR-T cells for cancer are unwanted tonic (antigen-independent) signaling and off-target activation. Efforts to overcome these hurdles have been blunted by a lack of mechanistic understanding. Here, we showed that single-cell analysis with time course mass cytometry provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 67 publications
4
35
0
Order By: Relevance
“…EF1a promoter resulted in bright CAR surface expression accompanied by non-antigen specific signalling, while this was not observed using CMV or truncated PGK promoters. Importantly, this observation with EF1a promoter was made using FMC63-based CD19 CAR previously described as free from tonic signalling [43,45]. Eyquem and colleagues further showed attenuation of CAR expression by targeting the CAR into the T-cell receptor alpha constant (TRAC) locus [69].…”
Section: Regulating Car Expression and Functionmentioning
confidence: 96%
See 2 more Smart Citations
“…EF1a promoter resulted in bright CAR surface expression accompanied by non-antigen specific signalling, while this was not observed using CMV or truncated PGK promoters. Importantly, this observation with EF1a promoter was made using FMC63-based CD19 CAR previously described as free from tonic signalling [43,45]. Eyquem and colleagues further showed attenuation of CAR expression by targeting the CAR into the T-cell receptor alpha constant (TRAC) locus [69].…”
Section: Regulating Car Expression and Functionmentioning
confidence: 96%
“…By expressing chimeric co-stimulatory receptors against target antigens to provide co-stimulation in trans, the engineered cells can mount effective responses against tumour cells expressing the target antigen whilst ignoring normal tissues expressing the same target antigen at the same levels [133]. Indeed, single cell signalling studies performed with this model system has demonstrated a lack of tonic signalling, which is linked with the absence of expression of exhaustion markers [45].…”
Section: Beyond Basic Logic; Sequential Logic Gates and Molecular Swimentioning
confidence: 99%
See 1 more Smart Citation
“…This precise discrimination provides a safeguard for solid tumours that lack tumour-specific antigens. Additionally, separating co-stimulatory signals can abrogate tonic signalling, mirrored by potent effector functions and lower exhaustion marker expression [ 25 ]. This feature may prolong the in vivo persistence of the gene-modified T cells.…”
Section: γδ T Cellsmentioning
confidence: 99%
“…Using “AND gate” system, which divides the signals, CCR γδ T cells were activated and released cytokines only when both CD3 and CCR receptors were engaged, whereas in CAR γδ T cells only CAR activation was sufficient. Using single-cell signaling analysis and mass cytometry (CyTOFF), which allowed a detailed characterization of the CAR signaling, they demonstrated that CCR in γδ T cells induced minimal baseline activity of CD3ζ-associated kinases in the absence of the antigen, meaning that tonic signaling decreased and the network plasticity increased [ 100 ]. This approach can ameliorate engineered T cells exhaustion and off-target cytotoxicity, features that affect consistently the clinical efficacy of CAR-T cells [ 40 ] ( Figure 1 ).…”
Section: γδ T Cell Engineering Strategiesmentioning
confidence: 99%